EXPOSE-R2: The Astrobiological ESA Mission on Board of the International Space Station - Rabbow, Elke; Rettberg, Petra; Parpart, Andre; Panitz, Corinna; Schulte, Wolfgang; Molter, Ferdinand; Jaramillo, Esther; Demets, René; Weiß, Peter; Willnecker, Rainer (Frontiers in Microbiology, 2017)
On July 23rd, 2014, the Progress cargo spacecraft 56P was launched from Baikonur to the International Space Station ISS, carrying EXPOSE-R2, the 3rd ESA (European Space Agency) EXPOSE facility, the second EXPOSE on the outside platform of the Russian Zvezda module, with 4 international astrobiological experiments into space. More than 600 biological samples of archaea, bacteria (as biofilms and in planktonic form), lichens, fungi, plant seeds, triops eggs, mosses and 150 samples of organic compounds were exposed to the harsh space environment and to parameters similar to those on the Mars surface. Radiation dosimeters distributed over the whole facility complemented the scientific payload. Three extravehicular activities later the chemical samples were returned to Earth on March 2nd, 2016, with Soyuz 44S, having spent 588 days in space. The biological samples arrived back later, on June 18th 2016, with 45S, after a total duration in space of 531 days. The exposure of the samples to Low Earth Orbit (LEO) vacuum lasted for 531 days and was divided in two parts: protected against solar irradiation during the first 62 days, followed by exposure to solar radiation during the subsequent 469 days. In parallel to the space mission, a Mission Ground Reference (MGR) experiment with a flight identical Hardware and a complete flight identical set of samples was performed at the premises of DLR in Cologne by MUSC, according to the mission data either downloaded from the ISS (temperature data, facility status, inner pressure status) or provided by RedShift Design and Engineering BVBA, Belgium (calculated ultra violet radiation fluence data). In this paper, the EXPOSE-R2 facility, the experimental samples, mission parameters, environmental parameters and the overall mission and MGR sequences are described, building the background for the research papers of the individual experiments, their analysis and results.